Lightning modelling for the research of forest fire ignition in Portugal - Couto, Flavio (2021)
The study aims to assess the applicability of the current Meso-NH electrical scheme (CELLS) in the investigation of forest fire ignition. Therefore, the challenge is to diagnose cloud-to-ground (CG) lightning at 1 km spatial resolution and, subsequently, preferred regions where Forest Fire Events (FFE) could be naturally ignited. The afternoon of 17th June 2017 has been considered for the study, since the dry thunderstorm environment configured a perfect scenario for natural ignition and evolution of some fires. The Pedrógão Grande wildfire ignited in this period and was the deadliest single fire event in the Portuguese history, with at least 60 people killed. The available observational data are used to validate the numerical results and to provide a brief characterization of the meteorological environment when jointly analysed with the simulation. In addition, cloud microphysics and cloud electrical structure are explored from the model results. The spatial distribution of the simulated CG lightning showed a good agreement with the lightning strokes obtained from the national lightning detection network. Overall, this paper introduces a possible application of the Meso-NH electrical scheme, namely the study of forest fire ignition by lightning strokes.